Anogenital warts and condom use–a survey of information giving. Issue 3 (June 1997) - McClean, H L; Hillman, R J
Abstract : OBJECTIVE: To examine information giving by genitourinary medicine (GUM) consultants about the use of condoms for patients with anogenital warts (AGW). METHOD: 228 GUM consultants in the UK and Ireland were sent a questionnaire concerning the information about condom use which they usually discuss with patients with AGW. The survey was carried out in 1994. RESULTS: There was a 46% response rate. Most consultants indicated giving information specifically with regard to the prevention of transmission of human papilloma virus (HPV), and not only in the context of safe sex. With regard to current AGW, consultants were more likely to discuss, than not to discuss, use of condoms with patients with regular sexual partners in terms of benefit, uncertain benefit, or no benefit. However, no significant difference in the likelihood of discussing, or not discussing, these issues was found for current AGW for patients without regular partners. For both groups, benefit of using condoms for current AGW was more likely to be discussed than no benefit. The majority of consultants indicated that they would discuss condom use after disappearance of AGW as being of uncertain benefit. However, many consultants also indicated discussing use of condoms for a specific period or an indefinite period of time, including many of those who specific discussing uncertain beneficial use of condoms after disappearance of AGW. The most common duration of condom use chosen for discussion was until 3 months after disappearance of AGW. CONCLUSION: GUM consultants vary in the information they give about condom use specifically to prevent transmission of HPV. This survey suggests a need for evaluation by GUM physicians of management guidelines relating to information given about condom use for AGW, including utilising the available scientific evidence as well as dealing with issues of uncertainty.